TINGKAT KEPUASAAN WISATAWAN MANCANEGARA TERHADAP KUALITAS PELAYANAN REKREASI AIR PT PANDAWA MARINE ADVENTURS DI TANJUNG BENOA - Udayana Pidada, Ida Bagus (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 01, July 2018, 2018)
PT Pandawa Marine Adventures is a company that is operated in the sector of marine tourism as a place for water recreation which is very popular among the travellers for playing water sport activities in the area of Tanjung Benoa. This study aims to analyse customer satisfaction related to the service quality of PT Pandawa Marine Adventures. The research used 100 respondents selected as the samples by using accidental sampling method. The collected data were then analyzed by descriptive qualitative method.The result of this study show that the tourists satisfaction related to the quality service of PT Pandawa Marine Adventures were measured into five satisfaction dimensions (tangible, reliability, responsiveness, assurance, empathy) by using 20 variables. The tangible dimension with four variables obtaining average value as amount 4,18 with satisfied category. Reliability with three variables obtaining average value as amount 4,06 with satisfied category. Responsiveness has six variables obtaining average value as amount 4,09 with satisfied category. Assurance has four variables and obtaining average value 4,07 with satisfied category. Empathy has three variables and obtaining average value 4,27 with very satisfied category.